Composition and diversity of plants in homrgardens in the community of Genipaúba, Santa Bárbara do Pará, Brazil - Moraes, Janielen Lopes; Costa, Karla Juliana Silva da; Rayol, Breno Pinto (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2024)
Agroforestry homegardens are considered older land use systems, traditionally practiced by family members who manage a diversity of plants around their residences for various purposes. The objective of this study was to evaluate the richness and floristic composition of agroforestry homegardens in the Genipaúba community, located in the municipality of Santa Bárbara, Pará state. Twenty homegardens were analyzed, selected through convenience sampling, taking into consideration the availability of the homegarden maintainers. Botanical identification was conducted on-site. Phytosociological parameters (frequency and density) were used to estimate horizontal structure, while Shannon-Wiener Index and Pielou's Evenness were used to estimate homegarden diversity. Eighty-four plant species distributed across 49 botanical families were identified, with Arecaceae being the family with the highest number of individuals (130). The most common species among the homegardens were Theobroma grandiflorum (cupuaçu) and Euterpe oleracea (açaí), which also had the highest relative frequencies of 7.33% and 6.47%, respectively. Regarding life form, the arboreal stratum had the highest predominance. The most prominent category of use in the Genipaúba homegardens was food. The calculated Shannon-Wiener Index for the agroforestry homegardens indicated a high diversity of species within these areas. The homegardens exhibited high richness and diversity.